2019
DOI: 10.12972/kjhst.20190008
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus and Citronella Essential Oils Used in Preservative Solutions Affect the Vase Life of Cut Philodendron Leaves

Nipaporn Yonsawad,
Montinee Teerarak

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…These results are in harmony with Yonsawad and Teerarak (2019) and Soliman et al, (2022b), who suggested that the essential oil may trigger higher antioxidant enzyme activity such as (POD, CAT or SOD), limiting the prospect for further free radical production of H 2 O 2 . Additionally, the activity of enzymes is controlled due to the antioxidant properties of plant essential oils, which are correlated with the senility of cut flowers.…”
Section: Chemical Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in harmony with Yonsawad and Teerarak (2019) and Soliman et al, (2022b), who suggested that the essential oil may trigger higher antioxidant enzyme activity such as (POD, CAT or SOD), limiting the prospect for further free radical production of H 2 O 2 . Additionally, the activity of enzymes is controlled due to the antioxidant properties of plant essential oils, which are correlated with the senility of cut flowers.…”
Section: Chemical Analysissupporting
confidence: 88%
“…MOE appears to be an efficient, friendly floral preservative due to its contents, as further detailed below. However, the essential oils of the Eucalyptus plant (EEO) are one of the most attractive essential oil for treating wound infections and has market potential as shelf life longevity via increasing the postharvest parameters of these cut flowers (Yonsawad and Teerarak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nonenzymatic antioxidants such as anthocyanin constitute an endogenous defense against ROS in flower tissues, with anthocyanin also contributing to petal color [ 66 ]. Many studies on cut flowers have demonstrated that natural antioxidants, including essential oils [ 67 , 68 ], salicylic acid [ 69 ], and moringa extract [ 70 ], delay senescence and extend vase life by increasing ROS scavenging activity; this also helps the flower retain anthocyanin content. In peppermint essential oil, the most powerful free radical scavenging compounds are menthone and isomenthone [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%